2019
DOI: 10.1177/0743558419883360
|View full text |Cite
|
Sign up to set email alerts
|

Discovering One’s Own Way: Adolescent Girls’ Different Pathways Into and Out of Self-Harm

Abstract: Self-harm is associated with mental illness and suicide risk. The present study aims to increase knowledge of adolescent girls’ pathways into and out of self-harm. The participants were 19 girls, 13 to 18 years of age, who were strategically selected from an outpatient care unit. A naturalistic multiple case study was done with personal interviews. The interviews were analyzed using Interpretative Phenomenological Analysis, and the capacity for “mentalization”—representation of behavior in terms of mental stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…They found several subjective experienced precipitating factors and triggers for self-harm which may increase knowledge of their need to self-harm, such as distressing emotions, sense of isolation, exposure to self-harm, relationship difficulties, social comparison, and school/work difficulties. Another recent qualitative study, Stänicke et al ( 2019 ) highlights how young girls in a clinical sample experience common aspects and different pathways into and out of self-harm. All girls began self-harming because of difficult feelings and relational problems but described their problems differently – as a way to handle self-criticism, diffuse stress, or earlier traumatic events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found several subjective experienced precipitating factors and triggers for self-harm which may increase knowledge of their need to self-harm, such as distressing emotions, sense of isolation, exposure to self-harm, relationship difficulties, social comparison, and school/work difficulties. Another recent qualitative study, Stänicke et al ( 2019 ) highlights how young girls in a clinical sample experience common aspects and different pathways into and out of self-harm. All girls began self-harming because of difficult feelings and relational problems but described their problems differently – as a way to handle self-criticism, diffuse stress, or earlier traumatic events.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, regarding autonomy as a possible developmental challenge during adolescence, they underlined how they discovered their own way out of self-harm. Further, they described different ways out of self-harm – by being understood and developing self-supporting monologs, by sharing experiences and trying coping-strategies, or by being respected and receiving practical support (Stänicke et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…I en kvalitativ studie med en fortolkende fenomenologisk analyse (Interpretativ phenomenological analysis) (Smith, 2008) ble 19 ungdommer (12-18 år) intervjuet om deres opplevelse av egen selvskading. Selv om alle fikk poliklinisk behandling var det ingen som uttrykte at de begynte i behandling fordi de selv ønsket å slutte å skade seg (Stänicke et al, 2019). For ungdommene var det ikke selvskadingen som var problemet.…”
Section: Et Eksempel På Heterogenitet -Ulike Veier Inn Og Ut Av Selvskadeunclassified
“…Qualitative research can complement context-independent results from quantitative studies by exploring with open questions how youths' make sense of everyday life and how self-harm and mental health problems are related to involvement in self-harm content online. The present study follows up with a group of young people (aged 18-23), 5 years after participating in a qualitative interview study exploring their ways into and out of self-harm (Stänicke et al, 2020). Having previously identified that they were influenced by peers and self-harm content online in their choice to self-harm as adolescents, the now young adults reflect on their lived experience of online self-harm activities.…”
Section: Introductionmentioning
confidence: 99%